Preparation method and application of polymer-based sulfur quantum dot water treatment agent

By using water bath method and hydrogen peroxide etching method in the preparation of sulfur quantum dots, combined with specific polymers as dispersants, the problems of cumbersome preparation and low conversion rate are solved, and polymer-based sulfur quantum dot water treatment agent is realized efficient preparation and effective application in industrial water.

CN119320634APending Publication Date: 2025-01-17NINGBO KANGMING ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411869505.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing sulfur quantum dot preparation methods have problems such as long synthesis cycle, cumbersome preparation, low conversion rate and inability to produce on a large scale, making it difficult to effectively inhibit mineral scale deposition and bacterial growth in industrial water treatment.

Method used

Using the water bath method, polymers such as acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer, polyaspartic acid, polyepoxysuccinic acid and other polymers were used as dispersants, and the hydrogen peroxide etching method was short-term scaled Synthesize polymer-based sulfur quantum dot water treatment agents, simplify the process and optimize the reaction conditions.

Benefits of technology

The prepared polymer-based sulfur quantum dot water treatment agent has short preparation cycle, high conversion rate, good water solubility and fluorescent properties, which can effectively inhibit the growth of mineral scale and bacteria in industrial water, and is suitable for industrial production and market applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320634A_ABST
    Figure CN119320634A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of nano fluorescent materials, and particularly relates to a preparation method and application of a polymer-based sulfur quantum dot water treatment agent. The preparation method comprises the following steps: (1) adding sulfur powder and a dispersing agent into an alkaline solution to prepare a mixed solution; (2) putting the mixed solution obtained in the step (1) into a water bath at 70-90 DEG C, heating, stirring and reacting for 15-20 minutes, and then adding an etching solvent; and (3) continuously reacting for 5-6 hours until the reaction is finished, adding the etching solvent again, and keeping the temperature for 0.5-1 hour to obtain a brownish red solution which is the sulfur quantum dot water treatment agent. The preparation method of the polymer-based sulfur quantum dot water treatment agent has the advantages of simple process, short preparation time, mild reaction conditions, low energy consumption, low cost and the like, and the prepared fluorescent sulfur quantum dot water treatment agent is simple in component and good in water solubility, can be used for inhibiting mineral scales and bacteria in industrial water, and has good application prospects. The concentration of the water treatment agent is monitored and controlled on line, and industrial production and market application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano fluorescent material preparation, and specifically relates to a preparation method of a polymer-based sulfur quantum dot water treatment agent and application of the same in industrial water treatment. Background Art

[0002] During the operation of industrial water treatment systems, mineral scale, algae and corrosion are prone to occur, which reduces the treatment efficiency and service life of the water system, and directly affects the integrity, reliability and safety of the industrial water system. Water treatment agents are one of the most widely used and simplest treatment methods, often including scale inhibitors, bactericides, fluorescent agents, etc. The polymer water treatment agents developed in recent years have good biodegradability, but are expensive, have poor high temperature resistance, and are used in high concentrations. At the same time, existing bactericides are mostly derived from the fields of pesticides and medicines, such as insecticides, disinfectants and mildew inhibitors, which are generally toxic or hazardous products and pose an environmental pollution risk in industrial water treatment. Fluorescent tracers used in water treatment monitoring, such as pyrene and pyrene derivatives, are gradually being eliminated because they are difficult to degrade. Therefore, the development of a new generation of environmentally friendly and multifunctional compounds is an important direction for the development of water treatment agents.

[0003] Sulfur quantum dots (SQDs) are a new type of metal-free quantum dots. They are used in optical sensing, cell imaging, photocatalysis and other fields due to their small size, excellent water solubility, biocompatibility, low toxicity, high photoluminescence quantum yield and excellent photostability. SQDs are composed of a sulfur polymer core and a large number of surface functional groups. The surface functional groups have good solubility, stability and easy functionalization. The selection of -COOH, -OH, -NH2, -CONH2 and other functional groups that have an inhibitory effect on mineral scale can make them have a good ability to inhibit the deposition of mineral scale. Sulfur itself has strong antibacterial properties. Therefore, it is expected to become a new generation of multifunctional water treatment agents for controlling scaling, antibacterial, and online monitoring of agent concentration and distribution in industrial water treatment.

[0004] At present, the synthesis of sulfur quantum dots is mostly concentrated on preparation processes such as hydrothermal method, ultrasonic microwave assisted method, oxygen acceleration method, and one-pot method, but these methods have defects such as long synthesis cycle, cumbersome preparation, low conversion rate and solid content. CN111978954A uses hydrogen peroxide-assisted top-down water bath method to synthesize blue fluorescent sulfur quantum dots, but anti-solvent is required to precipitate the sulfur quantum dots to obtain sulfur quantum dot powder, which is time-consuming and adds additional economic costs; CN115746832A uses oxygen acceleration method to prepare a water-soluble fluorescent sulfur quantum dot using polyethylene glycol (PEG) as a surface dispersant, but the preparation process requires oxygen atmosphere, the synthesis cycle is long and the dialysis cost is increased, and it cannot be produced quickly in a short time.

[0005] In the reported preparation of sulfur quantum dots, the dispersants are mostly concentrated on hydroxyl-rich molecules such as polyethylene glycol. Compared with these molecules, acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer and other polymers such as polyaspartic acid, polyacrylic acid and polyepoxysuccinic acid all show excellent water solubility and excellent performance in water treatment applications. The molecular surfaces of these polymers are rich in carboxyl and sulfonic acid groups, which not only endows the materials with rich negative charges, but also lays a solid foundation for the development of sulfur quantum dot water treatment agents based on these polymers for use in industrial water treatment.

[0006] In view of the problems of the current preparation methods of sulfur quantum dots, such as cumbersome preparation, long reaction cycle, low fluorescence yield and inability to scale production, we explored the use of a water bath method, using acrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer, polyaspartic acid, polyepoxysuccinic acid and polyacrylic acid as dispersants, to synthesize a new generation of polymer-based sulfur quantum dot water treatment agents on a short-term and large-scale basis. This water treatment agent has broad application potential in inhibiting mineral scale deposition in industrial water, inhibiting bacterial growth and monitoring agent concentration. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a polymer-based sulfur quantum dot water treatment agent in view of the deficiencies of the prior art. Another purpose of the present invention is to provide the application of the above-mentioned polymer-based sulfur quantum dot water treatment agent in industrial water treatment. The preparation method of the present invention has the advantages of simple process, mild reaction conditions, low cost, etc.; the prepared different polymer-based sulfur quantum dots are applied to the inhibition test experiment of mineral scale and bacteria, and have excellent inhibitory effects on mineral scale and bacteria in industrial water, long fluorescence luminescence duration period, strong fluorescence antioxidant ability, and have good industrial production and market application prospects.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a method for preparing a polymer-based sulfur quantum dot water treatment agent, comprising the following steps: (1) Adding sulfur powder and dispersant into an alkaline solution to prepare a mixed solution; (2) placing the mixed solution obtained in step (1) in a water bath at 70-90°C and stirring for 15-20 min before adding an etching solvent; (3) After the reaction is continued for 5-6 hours, the etching solvent is added again and kept warm for 0.5-1 hour to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

[0009] Preferably, in step (1), the mass ratio of sulfur powder to dispersant is (1.2-1.5):1.

[0010] Preferably, the sulfur powder in step (1) is one or a combination of more than one of sublimated sulfur, elemental sulfur, elastic sulfur, orthorhombic sulfur, rhombic sulfur and sulfur powder.

[0011] Preferably, the dispersant in step (1) is one or a combination of more than one of acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer, polyaspartic acid, sodium polyepoxysuccinate, and polyacrylic acid.

[0012] Preferably, the alkaline solution in step (1) is an aqueous sodium hydroxide solution or an aqueous sodium carbonate solution, and the concentration is 3.6 mol / L - 5.9 mol / L.

[0013] Preferably, the etching solvent in step (2) and step (3) is one or a combination of hydrogen peroxide solution and sodium percarbonate solution, with a concentration of 25%-50%, and the volume ratio of the etching solvent added in step (2) to the volume ratio of the etching solvent added in step (3) is 1:(3.5-5).

[0014] The second aspect of the present invention provides a polymer-based sulfur quantum dot water treatment agent prepared according to the above-mentioned preparation method of the polymer-based sulfur quantum dot water treatment agent.

[0015] The third aspect of the present invention provides an application of the above-mentioned polymer-based sulfur quantum dot water treatment agent in industrial water treatment.

[0016] Preferably, the application is for the inhibition of mineral scale in industrial water.

[0017] Preferably, the application is for monitoring water treatment chemicals in industrial water.

[0018] Preferably, the application is for inhibiting bacteria in industrial water.

[0019] The performance evaluation methods for the inhibition of mineral scale and bacteria and the online fluorescence monitoring of water treatment agents are as follows: The polymer-based sulfur quantum dot water treatment agent was prepared into a solution of a certain concentration, and the polymer-based sulfur quantum dot water treatment agent was evaluated for its calcium carbonate scale inhibition, calcium sulfate scale inhibition, antibacterial and fluorescence properties; the evaluation method for calcium carbonate scale inhibition performance was evaluated using the national standard of the People's Republic of China "GB / T 16632-2019 Determination of Scale Inhibition Performance of Water Treatment Agents - Calcium Carbonate Deposition Method"; the evaluation method for calcium sulfate scale inhibition performance was evaluated using the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-2020 General Technical Conditions for Scale Inhibitors for Oil Fields"; the agar plate method was used to evaluate the antibacterial effect of the sulfur quantum dot water treatment agent; and a static steady-state fluorescence spectrometer was used to monitor the fluorescence performance of the sulfur quantum dot water treatment agent.

[0020] The technical features and beneficial effects of the present invention are as follows: 1. The present invention provides a method for preparing a polymer-based sulfur quantum dot water treatment agent that is simple, easy to operate, has economical raw materials, and has a high conversion rate, and is suitable for industrial production. The method can prepare a polymer-based sulfur quantum dot water treatment agent with a size between 2 and 10 nm in just a few hours, and has the advantages of a short preparation cycle, high yield, and high fluorescence quantum yield.

[0021] 2. In the method for preparing polymer-based sulfur quantum dots of the present invention, by selecting a polymer with excellent water solubility as a dispersant, the reaction system of the present invention can be better used compared to polyethylene glycol, a dispersant commonly used in the preparation of quantum dots, thereby improving the dispersion performance of the polymer-based sulfur quantum dot water treatment agent in the reaction system and preventing the problem of aggregation-induced quenching due to aggregation. At the same time, in the method of the present invention, by adding a specific etching solvent in two steps, the surface morphology of the polymer-based sulfur quantum dot water treatment agent is changed, thereby further improving and optimizing its optical properties.

[0022] 3. The polymer-based sulfur quantum dot water treatment agent prepared by the preparation method of the present invention has excellent water solubility and dispersibility, and has a significant inhibitory effect on mineral scale and bacteria in industrial water. Its excellent fluorescence properties can accurately measure the concentration of the agent and realize online monitoring of the agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Transmission electron microscope (TEM) images of the polymer-based sulfur quantum dot water treatment agent prepared in Example 1 of a method for preparing a polymer-based sulfur quantum dot water treatment agent at different sizes; (a) 100 nm; (b) 50 nm; (c) 20 nm; (d) 10 nm; (e) 5 nm; and (f) 2 nm.

[0024] Figure 2 This is a particle size distribution diagram of sulfur quantum dots prepared in Example 1 of a method for preparing a polymer-based sulfur quantum dot water treatment agent, where the abscissa is size and the ordinate is percentage.

[0025] Figure 3 This is a fluorescence spectrum of the sulfur quantum dot water treatment agent prepared in Example 1 of a method for preparing a polymer-based sulfur quantum dot water treatment agent; wherein the abscissa is the wavelength, the ordinate is the fluorescence intensity, the excitation wavelength is 360 nm, and the emission wavelength is 410 nm.

[0026] Figure 4The present invention is a fluorescence spectrum diagram of the sulfur quantum dot water treatment agent prepared in Example 1 of a method for preparing a polymer-based sulfur quantum dot water treatment agent at different concentrations; wherein the abscissa is the wavelength, the ordinate is the fluorescence intensity, the excitation wavelength is 358 nm, and the emission wavelength is 411 nm; (a) 0.1 mg / L excitation spectrum; (b) 0.1 mg / L emission spectrum; (c) 0.2 mg / L excitation spectrum; (d) 0.2 mg / L emission spectrum; (e) 0.3 mg / L excitation spectrum; (f) 0.3 mg / L emission spectrum; (g) 0.4 mg / L excitation spectrum; (h) 0.4 mg / L emission spectrum.

[0027] Figure 5 The present invention is an X-ray diffraction (XRD) diagram of the sulfur quantum dot water treatment agent prepared in Example 1 of a method for preparing a polymer-based sulfur quantum dot water treatment agent for inhibiting calcium carbonate scale in industrial water; a is an X-ray diffraction diagram without adding the polymer-based sulfur quantum dot water treatment agent; b is an X-ray diffraction diagram with adding the polymer-based sulfur quantum dot water treatment agent.

[0028] Figure 6 The present invention is an X-ray diffraction (XRD) diagram of the sulfur quantum dot water treatment agent prepared in Example 1 of a method for preparing a polymer-based sulfur quantum dot water treatment agent for inhibiting calcium sulfate scale in industrial water; a is an X-ray diffraction diagram without adding the polymer-based sulfur quantum dot water treatment agent; b is an X-ray diffraction diagram with adding the polymer-based sulfur quantum dot water treatment agent.

[0029] Figure 7 The figures are the experimental effect diagrams of the inhibition of bacteria in industrial water by the sulfur quantum dot water treatment agent prepared in Example 1 of the method for preparing a polymer-based sulfur quantum dot water treatment agent at different concentrations; a is a bacterial growth diagram without the addition of the polymer-based sulfur quantum dot water treatment agent; b is a diagram of the antibacterial effect of the sulfur quantum dot water treatment agent at a concentration of 5 mg / L; c is a diagram of the antibacterial effect of the sulfur quantum dot water treatment agent at a concentration of 10 mg / L; d is a diagram of the antibacterial effect of the sulfur quantum dot water treatment agent at a concentration of 15 mg / L; e is a diagram of the antibacterial effect of the sulfur quantum dot water treatment agent at a concentration of 25 mg / L; and f is a diagram of the antibacterial effect of the sulfur quantum dot water treatment agent at a concentration of 50 mg / L. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0031] Unless otherwise specified, the reagents and materials involved in the following examples are all commercially available products and can be purchased through commercial channels. Among them, sulfur powder was purchased from Suzhou Cangxin Biotechnology Co., Ltd., acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer, polyaspartic acid, polyacrylic acid and polyepoxysuccinic acid were purchased from Shandong Taihe Technology Co., Ltd., hydrogen peroxide was purchased from Nanjing Wanqing Chemical Glass Instrument Co., Ltd., and sodium hydroxide was purchased from Shanghai Titan Technology Co., Ltd.

[0032] Example 1 A method for preparing a polymer-based sulfur quantum dot water treatment agent comprises the following steps: (1) Weigh 29 g of sublimed sulfur powder, 80 mL of acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer (solid content 30%), and 200 mL of 5.9 mol / L sodium hydroxide solution into a 500 mL round-bottom flask to prepare a mixed solution; (2) The mixed solution obtained in step (1) was stirred in a 70°C water bath for 15 min, and then 2 mL of 30% hydrogen peroxide was added dropwise. The stirring reaction was continued for 5 h. After the reaction was completed, 7 mL of 30% hydrogen peroxide was added and the mixture was kept warm for 1 h to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

[0033] The prepared sulfur quantum dot water treatment agent was tested, and the TEM results ( Figure 1 ) shows that the prepared sulfur quantum dots are spherical, the particles are evenly distributed, and have good dispersibility. Particle size distribution of sulfur quantum dots ( Figure 2 ) showed that the average size of sulfur quantum dots was 2.79 ± 0.13 nm, with a size distribution of 2-3 nm. Figure 3 ) It can be seen that the prepared sulfur quantum dots have fluorescent properties, with an excitation wavelength of 360 nm and an emission wavelength of 410 nm.

[0034] The prepared polymer-based sulfur quantum dot water treatment agent is used to inhibit mineral scale and bacteria in industrial water, comprising the following steps: (1) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 15 mg / L and 1 mg / L, respectively. The performance of inhibiting calcium carbonate scale and calcium sulfate scale was evaluated in accordance with the national standard of the People's Republic of China "GB / T 16632-2019 Determination of scale inhibition performance of water treatment agents - Calcium carbonate deposition method" and the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-93 Performance evaluation method of scale inhibitors for oil fields".

[0035] When the sulfur quantum dot water treatment agent with a concentration of 15 mg / L was used to measure its scale inhibition performance against calcium carbonate scale, or when the sulfur quantum dot water treatment agent with a concentration of 1 mg / L was used to measure its scale inhibition performance against calcium sulfate scale, the XRD results ( Figure 5-Figure 6 ) showed that the diffraction peak intensity of calcium carbonate scale or calcium sulfate scale in industrial water was significantly reduced. When the concentration was 15 mg / L, the inhibition efficiency of calcium carbonate scale was 75%, and when the concentration was 1 mg / L, the inhibition efficiency of calcium sulfate scale was 90%.

[0036] (2) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 5 mg / L, 10 mg / L, 15 mg / L, 25 mg / L and 50 mg / L, and the inhibitory effect on bacteria in industrial water was evaluated according to the agar plate method. Figure 7 As shown, the inhibition rate of the aqueous solution of sulfur quantum dot water treatment agent on bacteria in industrial water increases with the increase of concentration. When the concentration of the added sulfur quantum dot water treatment agent is 25 mg / L, the inhibition efficiency of bacteria is about 76%. When the concentration of the added sulfur quantum dot water treatment agent is 50 mg / L, the inhibition efficiency of bacteria reaches 90%.

[0037] (3) The polymer-based sulfur quantum dot water treatment agent is prepared into an aqueous solution with a concentration of 0.1-0.4 mg / L, and the fluorescence performance of the sulfur quantum dot water treatment agent is monitored by a static steady-state fluorescence spectrometer. Figure 4 As shown in the figure, it can be seen that with the increase of the concentration of the sulfur quantum dot water treatment agent aqueous solution, the fluorescence intensity of the sulfur quantum dots gradually increases, indicating that it can be used for online fluorescence monitoring of water treatment agents in industrial water treatment.

[0038] Example 2 A method for preparing a polymer-based sulfur quantum dot water treatment agent comprises the following steps: (1) Weigh 16 g of sulfur powder, 40 mL of polyacrylic acid (solid content 30%), and 200 mL of 3.6 mol / L sodium hydroxide solution into a 500 mL round-bottom flask to prepare a mixed solution; (2) The mixed solution obtained in step (1) was stirred in a water bath at 80°C for 18 min, and then 3 mL of 27.5% hydrogen peroxide was added dropwise. The stirring reaction was continued for 6 h. After the reaction was completed, 11 mL of 27.5% hydrogen peroxide was added and kept warm for 0.5 h to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

[0039] The prepared polymer-based sulfur quantum dot water treatment agent is used to inhibit mineral scale and bacteria in industrial water, comprising the following steps: (1) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 20 mg / L and 0.8 mg / L, respectively. The performance of inhibiting calcium carbonate scale and calcium sulfate scale was evaluated according to the national standard of the People's Republic of China "GB / T 16632-2019 Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method" and the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-93 Performance evaluation method of scale inhibitors for oil fields". When the concentration was 20 mg / L, the inhibition efficiency of calcium carbonate scale was 90%, and when the concentration was 0.8 mg / L, the inhibition efficiency of calcium sulfate scale was 87%.

[0040] (2) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 50 mg / L, and the inhibitory effect on bacteria in industrial water was evaluated according to the agar plate method. At this time, the inhibitory efficiency on bacteria reached 90%.

[0041] (3) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 0.1-0.4 mg / L, and the fluorescence performance of the sulfur quantum dot water treatment agent was monitored using a static steady-state fluorescence spectrometer. The results showed that the fluorescence intensity of the sulfur quantum dot water treatment agent increased with the increase of the concentration of its aqueous solution.

[0042] Example 3 A method for preparing a polymer-based sulfur quantum dot water treatment agent comprises the following steps: (1) Weigh 14 g of elemental sulfur, 32 mL of polyaspartic acid (solid content 30%), and 200 mL of 4.1 mol / L sodium carbonate solution into a 500 mL round-bottom flask to prepare a mixed solution; (2) The mixed solution obtained in step (1) was stirred in a water bath at 85°C for 20 min, and then 3 mL of 30% sodium percarbonate was added dropwise. The stirring reaction was continued for 5 h. After the reaction was completed, 13 mL of 30% hydrogen peroxide was added and the mixture was kept warm for 1 h to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

[0043] The prepared polymer-based sulfur quantum dot water treatment agent is used to inhibit mineral scale and bacteria in industrial water, comprising the following steps: (1) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 17 mg / L and 0.6 mg / L, respectively. The performance of inhibiting calcium carbonate scale and calcium sulfate scale was evaluated according to the national standard of the People's Republic of China "GB / T 16632-2019 Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method" and the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-93 Performance evaluation method of scale inhibitors for oil fields". When the concentration was 17 mg / L, the inhibition efficiency of calcium carbonate scale was 82%, and when the concentration was 0.6 mg / L, the inhibition efficiency of calcium sulfate scale was 82%.

[0044] (2) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 30 mg / L, and the inhibitory effect on bacteria in industrial water was evaluated according to the agar plate method. At this time, the inhibition efficiency of bacteria reached 80%.

[0045] (3) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 0.1-0.4 mg / L, and the fluorescence performance of the sulfur quantum dot water treatment agent was monitored using a static steady-state fluorescence spectrometer. The results showed that the fluorescence intensity of the sulfur quantum dot water treatment agent increased with the increase of the concentration of its aqueous solution.

[0046] Example 4 A method for preparing a polymer-based sulfur quantum dot water treatment agent comprises the following steps: (1) Weigh 12 g of elastic sulfur, 30 mL of sodium polyepoxysuccinate (solid content 30%), and 200 mL of 4.5 mol / L sodium hydroxide solution into a 500 mL round-bottom flask to prepare a mixed solution; (2) The mixed solution obtained in step (1) was stirred in a 90°C water bath for 16 min, and then 2 mL of 50% hydrogen peroxide was added dropwise. The stirring reaction was continued for 6 h. After the reaction was completed, 10 mL of 50% hydrogen peroxide was added and the mixture was kept warm for 0.5 h to obtain a brown-red solution. The obtained brown-red solution was the sulfur quantum dot water treatment agent.

[0047] The prepared polymer-based sulfur quantum dot water treatment agent is used to inhibit mineral scale and bacteria in industrial water, comprising the following steps: (1) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 12 mg / L and 0.9 mg / L, respectively. The performance of inhibiting calcium carbonate scale and calcium sulfate scale was evaluated according to the national standard of the People's Republic of China "GB / T 16632-2019 Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method" and the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-93 Performance evaluation method of scale inhibitors for oil fields". When the concentration was 12 mg / L, the inhibition efficiency of calcium carbonate scale was 70%, and when the concentration was 0.9 mg / L, the inhibition efficiency of calcium sulfate scale was 89%.

[0048] (2) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 35 mg / L, and the inhibitory effect on bacteria in industrial water was evaluated according to the agar plate method. At this time, the inhibitory efficiency on bacteria reached 84%.

[0049] (3) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 0.1-0.4 mg / L, and the fluorescence performance of the sulfur quantum dot water treatment agent was monitored using a static steady-state fluorescence spectrometer. The results showed that the fluorescence intensity of the sulfur quantum dot water treatment agent increased with the increase of the concentration of its aqueous solution.

[0050] Example 5 A method for preparing a polymer-based sulfur quantum dot water treatment agent comprises the following steps: (1) Weigh 10 g of orthogonal sulfur, 24 mL of a mixed solution of acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer and polyacrylic acid (solid content 30%), and 200 mL of 5.2 mol / L sodium carbonate solution into a 500 mL round-bottom flask to prepare a mixed solution; (2) The mixed solution obtained in step (1) was stirred in a 75°C water bath for 17 min, and then 4 mL of 30% sodium percarbonate was added dropwise. The stirring reaction was continued for 6 h. After the reaction was completed, 16 mL of 30% sodium percarbonate was added and the mixture was kept warm for 40 min to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

[0051] The prepared polymer-based sulfur quantum dot water treatment agent is used to inhibit mineral scale and bacteria in industrial water, comprising the following steps: (1) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 13 mg / L and 0.2 mg / L, respectively. The performance of inhibiting calcium carbonate scale and calcium sulfate scale was evaluated according to the national standard of the People's Republic of China "GB / T 16632-2019 Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method" and the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-93 Performance evaluation method of scale inhibitors for oil fields". When the concentration was 13 mg / L, the inhibition efficiency of calcium carbonate scale was 73%, and when the concentration was 0.2 mg / L, the inhibition efficiency of calcium sulfate scale was 70%.

[0052] (2) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 27 mg / L, and the inhibitory effect on bacteria in industrial water was evaluated according to the agar plate method. At this time, the inhibition efficiency of bacteria reached 88%.

[0053] (3) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 0.1-0.4 mg / L, and the fluorescence performance of the sulfur quantum dot water treatment agent was monitored using a static steady-state fluorescence spectrometer. The results showed that the fluorescence intensity of the sulfur quantum dot water treatment agent increased with the increase of the concentration of its aqueous solution.

[0054] Example 6 A method for preparing a polymer-based sulfur quantum dot water treatment agent comprises the following steps: (1) Weigh 11 g of orthorhombic sulfur, 26 mL of a mixed solution of polyaspartic acid and sodium polyepoxysuccinate (solid content 30%), and 200 mL of 5.5 mol / L sodium hydroxide solution into a 500 mL round-bottom flask to prepare a mixed solution; (2) The mixed solution obtained in step (1) was stirred in a water bath at 80°C for 20 min, and then 5 mL of 30% hydrogen peroxide was added dropwise. The stirring reaction was continued for 5 h. After the reaction was completed, 18 mL of 30% hydrogen peroxide was added and the mixture was kept warm for 50 min to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

[0055] The prepared polymer-based sulfur quantum dot water treatment agent is used to inhibit mineral scale and bacteria in industrial water, comprising the following steps: (1) The polymer-based sulfur quantum dot water treatment agent was prepared into aqueous solutions with concentrations of 18 mg / L and 0.5 mg / L, respectively. The performance of inhibiting calcium carbonate scale and calcium sulfate scale was evaluated according to the national standard of the People's Republic of China "GB / T 16632-2019 Determination of scale inhibition performance of water treatment agents - calcium carbonate deposition method" and the petroleum and natural gas industry standard of the People's Republic of China "SY / T 5673-93 Performance evaluation method of scale inhibitors for oil fields". When the concentration was 18 mg / L, the inhibition efficiency of calcium carbonate scale was 85%, and when the concentration was 0.5 mg / L, the inhibition efficiency of calcium sulfate scale was 76%.

[0056] (2) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 20 mg / L, and the inhibitory effect on bacteria in industrial water was evaluated according to the agar plate method. At this time, the inhibitory efficiency on bacteria reached 70%.

[0057] (3) The polymer-based sulfur quantum dot water treatment agent was prepared into an aqueous solution with a concentration of 0.1-0.4 mg / L, and the fluorescence performance of the sulfur quantum dot water treatment agent was monitored using a static steady-state fluorescence spectrometer. The results showed that the fluorescence intensity of the sulfur quantum dot water treatment agent increased with the increase of the concentration of its aqueous solution.

[0058] In summary, the present invention adopts hydrogen peroxide etching method for short-term large-scale production of polymer-based sulfur quantum dot water treatment agent. The preparation method is short in time, the reaction conditions are mild, and the reaction is stable and safe. The prepared polymer-based sulfur quantum dot water treatment agent has the advantages of excellent water solubility, good photostability and precise control of fluorescence color. The prepared fluorescence-adjustable polymer-based sulfur quantum dots are used for online monitoring of the efficient inhibition and growth of mineral scale and bacteria in industrial water, and have broad application prospects.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a polymer-based sulfur quantum dot water treatment agent, characterized in that: The following steps are involved: (1) Adding sulfur powder and dispersant into an alkaline solution to prepare a mixed solution; (2) placing the mixed solution obtained in step (1) in a water bath at 70-90°C and stirring for 15-20 min before adding an etching solvent; (3) After the reaction is continued for 5-6 hours, the etching solvent is added again and kept warm for 0.5-1 hour to obtain a brown-red solution. The obtained brown-red solution is the sulfur quantum dot water treatment agent.

2. The method for preparing the polymer-based sulfur quantum dot water treatment agent according to claim 1, characterized in that: The mass ratio of sulfur powder to dispersant in step (1) is (1.2-1.5):

1.

3. The method for preparing the polymer-based sulfur quantum dot water treatment agent according to claim 1, characterized in that: The sulfur powder in step (1) is one or a combination of more than one of sublimated sulfur, elemental sulfur, elastic sulfur, orthorhombic sulfur, rhombic sulfur and sulfur powder.

4. The method for preparing the polymer-based sulfur quantum dot water treatment agent according to claim 1, characterized in that: In the step (1), the dispersant is one or a combination of more than one of acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer, polyaspartic acid, sodium polyepoxysuccinate, and polyacrylic acid.

5. The method for preparing the polymer-based sulfur quantum dot water treatment agent according to claim 1, characterized in that: The alkaline solution in step (1) is an aqueous sodium hydroxide solution or an aqueous sodium carbonate solution, and the concentration is 3.6 mol / L-5.9 mol / L.

6. The method for preparing the polymer-based sulfur quantum dot water treatment agent according to claim 1, characterized in that: The etching solvent in step (2) and step (3) is one or a combination of hydrogen peroxide solution and sodium percarbonate solution, with a concentration of 25% to 50%. The volume ratio of the etching solvent added in step (2) to the volume ratio of the etching solvent added in step (3) is 1:(3.5-5).

7. The polymer-based sulfur quantum dot water treatment agent prepared according to the preparation method of the polymer-based sulfur quantum dot water treatment agent according to any one of claims 1 to 6.

8. Use of the polymer-based sulfur quantum dot water treatment agent according to claim 7 in industrial water treatment.

9. The use according to claim 8, characterized in that: Used for the inhibition of mineral scale in industrial water.

10. The use according to claim 8, characterized in that: Used for monitoring water treatment chemicals in industrial water.

11. The use according to claim 8, characterized in that: Used for inhibiting bacteria in industrial water.

Citation Information

Patent Citations

  • Preparation method of water-soluble fluorescent sulfur quantum dots and application of water-soluble fluorescent sulfur quantum dots to detection of quercetin

    CN115746832A

  • Acrylic acid acrylamide copolymer furring-proof dispersant and preparing method thereof

    CN101033278A

  • Tungsten quantum-dot photocatalyst and preparation method thereof

    CN107377003A

  • Preparation method of sulfur quantum dots with blue fluorescence characteristics

    CN111978954A

  • Method for rapidly synthesizing high-fluorescence sulfur quantum dots

    CN112852412A

Cited By

  • Vanadium titano-magnetite grinding aiding process

    CN121155743A